WOMEN’S SOCIO-POLITICAL MOVEMENT IN GALICIA: MOSCOPHILES AND NARODOVTSI - Shtonda, Veronica (Young Scholars Grinchenko – Seton International Journal, 2026)
The women’s socio-political movement in Galicia in the 19th – 20th centuries was a distinctive phenomenon that combined the struggle for women’s rights with the aspiration to preserve the Ukrainian language, traditions, and culture under conditions of statelessness. This topic is important because it demonstrates how women became active participants in public life and helped safeguard national identity amid the pressures of Polonization and Russification. The study compares the two opposing currents within the women’s movement, the Moscophile and the Narodovtsi, and their impact on women’s roles in society. To achieve this, the historical-comparative method was employed, integrating analyses of scholarly works and of the activities of women’s organizations, education, and women’s economic engagement. The sources include the magazines “Lada”, “Rusalka”, and “Pershyi vinok”, along with foundational studies by contemporary historians, in particular Marta Bohachevsky-Chomiak, Stepan Kost, and Liliia Sholohon. A notable feature of the work is that the Narodovtsi movement integrated education, active female participation in civic life, and national interests, whereas the Moscophiles adhered to a conservative model in which women remained primarily at home, engaging only in charity and church activities without a broader national dimension. The research shows that the Narodovtsi trend ultimately prevailed and shaped the image of an educated, active, and nationally conscious woman. This contributed to the formation of Ukrainian women’s organizations, the advancement of education and the economy, and the laying of the groundwork for future Ukrainian statehood. The women’s movement in Galicia became a vital component of nation-building and social transformation, preparing the soil for the establishment of the “Soyuz Ukrainok” – the most powerful women’s organization in interwar Europe.